Tinjauan Pustaka Sistematis: Penanaman Nilai Karakter Kedisiplinan Melalui Pembiasaan Sholat Berjamaah di Sekolah Dasar - Nur Aisyah Amini; Muhamad Taufik Hidayat (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This study aimed to reveal the obstacles, strategies, and results of instilling a disciplinary character through congregational prayer in Indonesian elementary schools. The method used in this study was a systematic literature review. The information used contained an attitude of discipline. The literature review process began by searching for relevant articles, evaluating them by data extraction, and then comparing the results of the literature. The database used was Google Scholar. The results of this study indicate that (1) Obstacles to instilling discipline include parents who lack or have not followed up on school programs that have been implemented in schools, students who are still unaware, and a lack of infrastructure. (2) The strategy found in dealing with obstacles in instilling disciplinary character is imposing sanctions on students who refuse to pray. (3) The results of cultivating discipline through congregational prayer can improve student worship discipline. The implications of this study are as follows: First, the teacher can set an example for their students in cultivating the character of discipline through the habit of congregational prayer at school. Second, parents can monitor the program that has been implemented at school. Third, students can become accustomed to doing good things, which they can then apply in everyday life. This study revealed the cultivation of discipline in Indonesian elementary schools comprehensively.